Habitar a cidade: a (re) construção de espaços de habitação para ex-internos de um hospital psiquiátrico e sua importância para a produção de subjetividade - Renato Ferreira Franco (2012)
This study aims to analyze the importance of living space for the production of subjectivity. Therefore, this study was accompanying a group of residents of a psychiatric hospital on two occasions: first, during the process of deinstitutionalization and the second time when this group already living in therapeutic residential services. This is a qualitative research based on studies of Ethnography and Interpretive Anthropology. Reached the conclusion that the space is very important for subjectivity, but the living space is one that has more influence for the production of subjectivity. As concerns the living space, it should only be understood well when the subject through an active participation in its construction, appropriates it and uses it as a reference for exploring the city. The action to explore the city is fertile ground for the production of subjectivities and the achievement of citizenship.